Uwarunkowania konsumpcji artykułów spożywczych na przykładzie wyrobów mleczarskich i mięsnych - studium przypadku - Góralczyk, Marzena (Conditioning Consumption of Groceries on the Example of the Dairy and Meat Products - the Study of Case, 2006)
The conditioning of consumption of dairy and meat products are discussed in the article. An essential role of price and quality in the shopping decisions of customers is shown. In the light of the conducted questionnaire investigations it is stated that consumers attach the smallest weight on the market to the advertisement of products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 268-273